"Post‐It" Type Connected DNA Created with a Reversible Covalent Cross‐Link1. Issue 3 (28th November 2014) - Tomás‐Gamasa, María; Serdjukow, Sascha; Su, Meng; Müller, Markus; Carell, Thomas
Abstract We report the development of a new heterobase that is held together through reversible bonding. The so‐formed cross‐link adds strong stabilization to the DNA duplex. Despite this, the cross‐link opens and closes through reversible imine bonding. Moreover, even enzymatic incorporation of the cross‐link is possible. The new principle can be used to stabilize DNA duplexes and nanostructures that otherwise require high salt concentrations, which may hinder biological applications.